2022
DOI: 10.21203/rs.3.rs-1693288/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and Frequency of the Use of Nicotine Pouches and Its Association With Stress Amongst Students of Medical and Non-Medical Universities of Karachi, Pakistan

Abstract: BACKGROUND AND OBJECTIVES Oral Nicotine Pouches (NPs) are one of the fastest-growing products among young adults, being actively marketed by companies through catchy advertisements. Owing to the easy availability and concealed usage, there is a high chance that these could become an addiction very soon. The objective of our study was to assess the prevalence of Nicotine Pouch consumption and its association with the perceived stress of an individual being a reason behind its usage. METHODS A cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This prevalence is higher than the prevalence noted in a previous study from year 2021 on NPs from Pakistan. 17 This shows a rising trend in NP use across the country. This can potentially be explained by the unethical marketing practices; companies are promoting them as safe; their campaign is unregulated by the government and the national celebrities are promoting this product on social media without checking its safety.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This prevalence is higher than the prevalence noted in a previous study from year 2021 on NPs from Pakistan. 17 This shows a rising trend in NP use across the country. This can potentially be explained by the unethical marketing practices; companies are promoting them as safe; their campaign is unregulated by the government and the national celebrities are promoting this product on social media without checking its safety.…”
Section: Discussionmentioning
confidence: 97%
“…A study conducted by the Institute for Global Tobacco Control showed that 22% of tobacco vendors across 8 cities of Pakistan had 'Velo' products displayed at their stores and 13% of tobacco vendors had advertisements for 'Velo' posted at their point-of-sale. 17 The Pakistan National Heart Association (PANAH) strongly appealed the government to curb the increasing addiction of NPs in the youth stating that it contained harmful chemicals that can cause heart ailments, cancer, kidney diseases, or stunted growth. 21,22 Therefore, it is imperative to take measures to address the rising issue of NPs addiction amongst our youth.…”
Section: Discussionmentioning
confidence: 99%